1978
DOI: 10.1111/j.1476-5381.1978.tb08468.x
|View full text |Cite
|
Sign up to set email alerts
|

PHARMACOLOGICAL EVIDENCE FOR THE INVOLVEMENT OF Na+ CHANNELS IN THE RELEASE OF CATECHOLAMINES FROM PERFUSED ADRENAL GLANDS

Abstract: Veratridine (0.1 mM) was found to be effective in producing an increase in the catecholamine output from perfused guinea‐pig adrenal glands in the presence of high concentrations of hexamethonium (1.83 mM) and atropine (28.8 μM). The response to veratridine was abolished by removal of either Na+ or Ca2+ from perfusion media and by the addition of tetrodotoxin (0.1 μM). It is suggested that the response to veratridine may be due to an increase in the tetrodotoxin‐sensitive Na+ permeability of chromaffin cell me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 4 publications
9
19
0
Order By: Relevance
“…As already reported (Ito et al, 1978; Diference in the time course of release of catecholamine and dopamine /3-hydroxylate activity…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…As already reported (Ito et al, 1978; Diference in the time course of release of catecholamine and dopamine /3-hydroxylate activity…”
Section: Resultssupporting
confidence: 53%
“…Both adrenal glands were perfused and isolated following the general procedure described previously (Ito et al, 1978; Friedman & Kaufman (1965).…”
Section: Methodsmentioning
confidence: 99%
“…Table 2). In agreement with previous results (Teraoka et al, 1991) (20 mM (Douglas & Rubin, 1961;Ito et al, 1978;1979;Kilpatrick et al, 1981;Knight & Baker, 1983;Knight & Kesteven, 1983;Wakade & Wakade, 1983). However, the mechanism underlying the depolarization is different between stimulants, ACh and veratridine cause depolarization resulting mainly from the activation of nicotinic receptor channels and voltage-dependent, tetrodotoxin-sensitive Na' channels, respectively.…”
Section: Resultssupporting
confidence: 81%
“…Catecholamine secretion produced by these secretagogues required Ca ions in the incubation medium in which the cells were suspended. The results indicate that isolated adrenal chromaffin cells possess ACh receptors and Na+ channels, activation of which mediates Ca-dependent catecholamine secretion similar to the perfused adrenal glands of guinea-pig (Ito, Nakazato & Ohga, 1978.…”
Section: Resultsmentioning
confidence: 86%
“…Although the release of DBH -is considered to be an index of the exocytotic release of catecholamine from adrenal gland (Viveros et al 1968) and sympathetic neurones (De Potter, De Schaepdryver, Moerman & Smith, 1969), it has been reported that the time course of catecholamine secretion was different from that of concomitant DBH secretion in both tissues (Cubeddu et al 1974; Dixon et al 1975;Jacobs et al 158 S. ITO 1978;Edwards et al 1980;Ito et al 1980;Muscholl et al 1980). It may be possible that delayed output of DBH, compared with catecholamine secretion, results from a delayed washout of DBH from the release site into the circulation because of the presence of diffusion barriers for this large protein.…”
Section: Resultsmentioning
confidence: 99%